2009
DOI: 10.1080/01942630903011123
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Day-Camp Model of Modified Constraint-Induced Movement Therapy With and Without Botulinum Toxin A Injection for Children With Hemiplegia

Abstract: The objective of the study was to investigate the feasibility of modified constraint-induced (CI) therapy provided in a 2-week day-camp model with and without intramuscular botulinum toxin type A (BoNT-A) injections for children with congenital cerebral palsy. Sixteen children with congenital hemiplegia, Manual Ability Classification System (MACS) level I and II, aged 8-17 years, participated in a CI therapy day camp; of whom five participants (aged 11-16 years) received intramuscular BoNT-A prior to CI therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 28 publications
1
28
0
8
Order By: Relevance
“…This change does not exceed the SRD calculated in the present study, and may therefore constitute acceptable variability. In the second treatment group ('CI with BoNT-A', n = 5), the median JTTHF total score decreased by approximately 56 seconds in the pre-intervention period (Eliasson et al, 2009), far exceeding the SRD presented here. This decrease may also constitute acceptable reliability given that children with CP are a significantly more heterogeneous population than TDC with respect to the JTTHF, statistically leading to a larger SRD.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This change does not exceed the SRD calculated in the present study, and may therefore constitute acceptable variability. In the second treatment group ('CI with BoNT-A', n = 5), the median JTTHF total score decreased by approximately 56 seconds in the pre-intervention period (Eliasson et al, 2009), far exceeding the SRD presented here. This decrease may also constitute acceptable reliability given that children with CP are a significantly more heterogeneous population than TDC with respect to the JTTHF, statistically leading to a larger SRD.…”
Section: Discussionmentioning
confidence: 58%
“…In a feasibility study for an intervention model for children with CP, The JTTHF showed less stability than expected between pre-screening and baseline scores over a 4-month interval (Eliasson et al, 2009). In one of the two treatment groups ('CI', Downloaded by [University of Tasmania] at 09:33 01 October 2015 n = 11), the median JTTHF total score decreased by approximately 5 seconds over this pre-intervention period.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, we used the recently developed version of AHA for children or adolescents over 12 years of age (personal communication with Krumlinde-Sundholm, 23 February, 2015). This version requires adaptation of the test situation but can be used with the same scoring criteria, as previously demonstrated in several studies, including (Eliasson et al, 2009). The lack of published research into the psychometric prop-erties of the adolescents' version of AHA might be considered a limitation as might be the time lag that accompanied the AHA and CHEQ data collection.…”
Section: Discussionmentioning
confidence: 91%
“…It is unlikely that the functional improvement is only due to postoperative training, as Holmefur et al [28] have shown in a longitudinal study that children with CP above the age of 6 years have already reached their AHA score plateau. This means that it is not easy to achieve improvement of bimanual ability with only training within this age group even if the training intensity is high [40,41]. Clear training effect in this age group has only been seen after Constraint-induced movement therapy which is a very intensive type of training [42].…”
Section: Discussionmentioning
confidence: 95%